Social Impact of Microfinance on SHG Members: A Case Study of Manipur - Dhaneshwar Singh, N.; Ramananda Singh, H. (Prabandhan: Indian Journal of Management, 2012)
Manipur is one of the economically backward states and is located at the easternmost remote corner of India. Although microfinance movement is comparatively new in the state of Manipur, it is becoming increasingly popular in the rural areas of Manipur as well as in the other parts of the country. Formation of SHGs has become a movement in rural areas. There are 602 NGOs, out of which 70 NGOs are directly associated with microfinance and are involved in the socio-economic development of the rural and backward people of Manipur. These NGOs have been playing important role in giving both financial and nonfinancial support to poor people for taking up various income-generating activities. This paper attempts to highlight the social impact of microfinance on SHG members in terms of self-confidence level, ability to take decisions, social awareness and social responsibility, skill development, access to better health services and other social infrastructure facilities after joining the microfinance programme of the NGOs in the state of Manipur.